Quality of life in patients with transcatheter aortic valve implantation: an analysis from the INTERVENT project - Tamm, Alexander R.; Jobst, Marina L.; Geyer, Martin; Hahad, Omar; Buderus, Victoria; Schmidt, Alexander; Prochaska, Jürgen H.; Wild, Philipp S.; Treede, Hendrik; Münzel, Thomas; von Bardeleben, Ralph Stephan (Frontiers in Cardiovascular Medicine, 2023)
Background Transcatheter aortic valve implantation (TAVI) is a standard treatment for patients with aortic valve stenosis due to its very low mortality and complication rates. However, survival and physical integrity are not the only important factors. Quality of life (QoL) improvement is a crucial part in the evaluation of therapy success. Methods Patients with TAVI were questioned about their QoL before, one month and one year after the intervention as part of the INTERVENT registry trial at Mainz University Medical Center. Three different questionnaires were included in the data collection (Katz ADL, EQ-5D-5l, PHQ-D). Results We included 285 TAVI patients in the analysis (mean age 79.8 years, 59.4% male, mean EuroSCORE II 3.8%). 30-day mortality was 3.6%, complications of any kind occurred in 18.9% of the patients. Main finding was a significant increase in the general state of health measured on the visual analog scale by an average of 4.53 (± 23.58) points (BL to 1-month follow-up, p = 0.009) and by 5.19 (± 23.64) points (BL to 12-month follow-up, p = 0.016). There was also an improvement of depression symptoms, which was reflected in a decrease in the total value of the PHQ-D by 1.67 (± 4.75) points (BL to 12-month follow-up, p = 0.001). The evaluation of the EQ-5D-5l showed a significant improvement in mobility after one month (M = −0.41 (± 1.31), p < 0.001. Regarding the independence of the patients, no significant difference could be found. Apart from that, patients with risk factors, comorbidities or complications also benefited from the intervention despite their poor starting position. Conclusion We could show an early benefit of QoL in TAVI patients with significant improvement in the subjective state of health and a decrease in symptoms of depression. These findings were consistent over 1 year of follow up.